Rancang Bangun Stasiun Bumi Satelit Orbit Rendah Berbasis Radio Terdefinisi Perangkat Lunak pada 437 MHz - Hanifah, Nita; Fadhlul Ariqi; Khairan Rafi Sukma Pratama; Bambang Setia Nugroho; Edwar (Jurnal Serambi Engineering, 2024)
The aim of this research is to design and build a Software Defined Radio (SDR) based ground station for communication with low earth orbit (LEO) satellites at 437 MHz. This ground station is designed to overcome the challenges of high cost and hardware complexity in conventional satellite communications. Methods used include system development using two Yagi antennas as transmitters and receivers, and the use of Raspberry Pi and RTL-SDR for signal processing. Tests were conducted at Telkom University, Bandung, with results demonstrating the ground station's ability to effectively track and receive signals from multiple LEO satellites. The test results show that the system can operate well in the UHF frequency range, with stable signal reception despite some minor interference. The study concludes that the use of SDR can increase the flexibility and efficiency of satellite communications, and provides recommendations for further hardware and software improvements to improve satellite tracking accuracy.